Mrs Beeton fish & seafood - Beeton, Isabella and Baker, Gerard; Foreword By Hix, Mark (London Weidenfeld & Nicolson, 2012)
The complete guide to cooking fish and seafood by our most famous cook - fully updated for the 21st-century kitchen.
Including Colour Illustrations and Index
Keywords: Cooking (Seafood)